Cues for Key Perception of a Melody - Matsunaga, Rie; Abe, Jun-Ichi (Music perception, 2005)
STUDIES HAVE SHOWN THAT PITCH SET, which refers to a set of pitches of constituent tones of a melody, is a primary cue for perceiving the key of a melody. The present study investigates whether characteristics other than pitch set function as additional cues for key perception. In Experiment 1, we asked 13 musicians with absolute p itch t o select k eys for 60 stim ulus t one sequences consisting of the same pitch set differing in pitch sequence. In Experiment 2, we asked 31 nonmusicians to select tonal centers for the 60 stimulus tone sequences. Responses made by the musicians and the nonmusicians yielded essentially equivalent results, suggesting that key perception is never unique to musicians. The listeners' responses were limited to a few keys/tones, and some tone sequences elicited agreement among the majority of the listeners for each of the keys/tones. These findings confirm that key perception is not only defined by pitch set but also influenced by characteristics other than pitch set such as pitch sequence.